Shadow Woman [large type] : A Novel - Howard, Linda, 1950- (Thorndike Press, 2013)
Lizette Henry, possessing unusual detection skills but struggling with a memory disorder, accepts help from the mysterious and seductive Xavier--a stranger who triggers disturbing images of an unspeakable crime of which Lizette may or may not be the perpetrator.